(untitled) (International Journal of Sustainable Development & World Policy, 2019)
Industries, and Vehicles emit air pollutants; all among these pollutants Particulate Matter (PM) has the greatest effects on human health like respiratory diseases and effects on environment like global warming and climate change. To find the levels of ambient PM air pollutants in commercial and bus-stations areas of Gasabo-district, one of the three districts of Kigali the capital city Rwanda was the main purpose of this research. The Air Visual Nodes instruments were used to measure values of PM concentration in microgram per cubic-meter (µg/m3). Questionnaire method was used where the total of 125 respondents for all sites was randomly selected to respond some questions before starting sampling activity in July, 2018. Sampling showed that; In both Batsinda and Kinamba commercial areas, level of PM is between (20-60)µg/m3 for PM2.5 and (80-130)µg/m3 for PM10. While in both Kagugu and Gakinjiro (Gisozi) commercial areas level of PM is between (15-45)µg/m3 for PM2.5 and (50-110)µg/m3 for PM10. In Batsinda bus-station level of PM is between (25-60) µg/m3 for PM2.5 and (80-130)µg/m3 for PM10. While in Kakiru bus-station, level of PM is between (15-40)µg/m3 for PM2.5 and (80-120)µg/m3 for PM10. Interview showed vehicle and decomposition of waste materials emissions as source of air pollutants. World Health Organization Guideline indicate that 10µg/m3 for PM2.5 and 20µg/m3 for PM10 are adequate, these above findings are high compared to these guidelines that is why education for all toward good air quality would be the best option in reducing air pollutants in Kigali city.